The Influence of Social Media and Customer Testimonials on Consumer Trust in Victoria Brownies MSMEs, Bandar Lampung - Dewi, Ariska Citra; Meidasari, Evi; CN, Yudhinanto (LPPPIPublishing, 2026)
This study aims to determine and analyze the influence of social media and customer testimonials on consumer trust in UMKM Victoria Brownies Bandar Lampung. Consumer trust is an important factor in maintaining loyalty and increasing purchasing decisions, especially in digital-based culinary businesses. This study uses a quantitative method with an associative approach. The sample used was 100 respondents who were Victoria Brownies consumers, with a sampling technique using purposive sampling. The data analysis technique used was multiple linear regression with the help of the IBM SPSS 25 program. The results showed that social media had a significant effect on consumer trust with a t-value of 4.179 and a significance of 0.000. Customer testimonials also had a significant and dominant effect on consumer trust with a t- value of 13.250 and a significance of 0.000. Simultaneously, social media and customer testimonials had a significant effect on consumer trust with a calculated F value of 323.821 and a significance of 0.000. The coefficient of determination (R²) of 0.680 indicates that 68% of the variation in consumer trust can be explained by the two independent variables. Thus, it can be concluded that social media and customer testimonials are important factors that must be considered in building and increasing consumer trust, especially in the context of MSME digital marketing.